A NORMA ABNT NBR 16001 SISTEMA DE GESTÃO DA RESPONSABILIDADE SOCIAL COMO FERRAMENTA DE ESTRATÉGIA DE NEGÓCIO: UM ESTUDO DE CASO SERASA EXPERIAN - Ramos, Ana Júlia Guerra do Nascimento (2011)
The objective of this study is to analyze the benefits can use norm ABNT NBR 16001 requirements of system of management of the social responsibility in the strategy of the businesses of the certified organization. How many to the methods aspects the present study it possess bibliographical character, using itself the case study. Being thus, ABNT NBR 16001 searched on the basis of to describe the flow of the certification process; to present the historical evolution of the social responsibility in the world and Brazil, the main concepts of the organization with social responsibility, the paper of the interested people, as well as the importance in the systems of management of the norm of requirements of SGRS and certification; e to analyze the perceptions on the process of implantation of a system of management of the social responsibility based in norm ABNT NBR 16001, next to Serasa Experian, identifying proportionate benefits of the strategy of business for the certification. Therefore, one gives credit that by means of the implementation of the system on the basis of norm ABNT NBR 16001, the organization can acquire awareness concerning the importance to adopt action with social responsibility front to the society, and for result establishing confidence and motivation in the organization, with the evidence of the certification, between the interested people, being these, internal and external, investing, local community and consuming customers.